2015
DOI: 10.1186/s13046-015-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

MiR-203 down-regulates Rap1A and suppresses cell proliferation, adhesion and invasion in prostate cancer

Abstract: ObjectiveEvidence supports an important role for miR-203 in the regulation of the proliferation, migration and invasion of prostate cancer (PCa) cells. However, the exact mechanisms of miR-203 in PCa are not entirely clear.MethodsWe examined the expression of miR-203 in prostate cancer tissues, adjacent normal tissues, PCa cell lines and normal prostate epithelial cells by qRT-PCR. Then, the effects of miR-203 or Rap1A on proliferation, adhesion and invasion of PCa cells were assayed using CKK-8, adhesion anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 39 publications
6
43
0
Order By: Relevance
“…miR-203 is dysregulated in several cancers and it links to the tumor progression. For example, miR-203 is significantly downregulated in prostate cancer and renal cancer, and functions as a tumor suppressor by inhibiting cell proliferation, migration and invasion [38][39]. In studies of colorectal cancer, high levels of miR-203 were detected in CRC [40][41][42] and increased expression of miR-203 significantly inhibited proliferation, motility, as well as invasion of CRC cells [43], which is consistent with our data.…”
Section: Discussionsupporting
confidence: 90%
“…miR-203 is dysregulated in several cancers and it links to the tumor progression. For example, miR-203 is significantly downregulated in prostate cancer and renal cancer, and functions as a tumor suppressor by inhibiting cell proliferation, migration and invasion [38][39]. In studies of colorectal cancer, high levels of miR-203 were detected in CRC [40][41][42] and increased expression of miR-203 significantly inhibited proliferation, motility, as well as invasion of CRC cells [43], which is consistent with our data.…”
Section: Discussionsupporting
confidence: 90%
“…In glioblastoma, researchers demonstrated that Rap1A promotes glioblastoma proliferation and tumor growth [11]. Knocking down of Rap1A with miRNAs inhibited the Rac1/PAK1 pathway and attenuated prostate cancer cell proliferation, adhesion, and invasion [12,13]. These results suggest that Rap1A may exert its effect as an oncogene.…”
Section: Original Researchmentioning
confidence: 99%
“…In cancers miR‐203 has several anti‐tumoral functions. Up‐regulation of this miRNA leads to a reduced proliferation possibly by inducing cell cycle arrest . In addition, several studies showed that high levels of miR‐203 inhibit tumor cell migration and invasion and by this reduce the metastatic potential of tumors .…”
Section: Discussionmentioning
confidence: 99%